International Comparisons of Money Demand : A Review Essay - Boughton, James (IMF Working Papers; Working Paper, 1992)
Many studies of the demand for money, covering a wide variety of economies, have demonstrated the importance of financial innovations and shifts in monetary policy regimes, but they have also illustrated the difficulty of measuring and assessing such changes. Because innovations and regime shifts have differed markedly across countries, international comparisons can help identify their effects. This paper reviews the literature on money demand comparisons, focusing primarily on industrial countries. It finds that innovations have had widespread effects, but also that the demand for money is not generally less stable now than it was before those changes occurred.